Resource Development in Canada’s North: Impacts on Families and Communities (Journal of Comparative Social Work, 2014)
The growth of global economies, particularly in Asia, has resulted in an increased demand for natural resources. Canada is a large country rich in hydrocarbons and minerals, and the exploitation of these resources is a priority for Canadian provincial and federal governments. In their rush to reap the economic benefits of resource development, governments have concentrated on creating optimal conditions for the corporations that exploit and produce the resources in northern and remote regions of the country. The rapid promotion of development has meant that families and communities are usually given secondary consideration. The changes associated with resource development exert some serious negative effects on communities and families, and it is important for social workers to understand this reality in order to deliver service in an effective manner.This research used a case study method to examine three examples of the effects of resource development on families and communities in Canada: long distance commuting to the Athabaska oil sands and the effects on families in Newfoundland, diamond mining and the Tlicho people of Wekwee´ti´ in the Northwest Territories, and the large influx of construction workers to develop the processing and port facilities in the community of Kitimat in northwestern British Columbia. The results can inform social work education, as well as the practice of social workers located in remote communities affected by rapid resource development.